DISTRIBUSI SPASIAL DAN PREFERENSI HABITAT GASTROPODA DI KAWASAN HUTAN MANGROVE SEGARA ANAKAN, CILACAP - Kresnasari, Dewi; Gitarama, Arbi Mei; Subhan, Subhan (Jurnal Sapa Laut, 2022)
Ecologically, the mangrove ecosystem acts as a spawning ground, nursery ground and feeding ground for various organisms. One of the biota located in the Segara Anakan mangrove ecosystem is Gastropods. This fauna plays an important role in food webs and decomposition processes. The Segara Anakan mangrove forest has undergone changes due to natural factors (sedimentation) and anthropogenic factors. If this is ignored, of course, it will affect the distribution pattern and habitat preferences. The purpose of this study was to determine the composition, abundance, distribution and habitat preferences of gastropods in the mangrove forest of Segara Anakan, Cilacap. The study was conducted in AugustOctober 2022 with a sampling period of once every two weeks. The sampling method used is purposive sampling. Two locations were selected based on different characteristics, namely: St A (eastern part of Segara Anakan, salinity 10-20 , density of mangrove Rhizophora sp. dense, close to the port) and St B (western part of Segara Anakan, salinity 5-10‰, mangrove density Rhizophora sp. is rare, close to residential areas). At each research station, five sampling points were determined, each point contained three sampling plots. The data obtained were analyzed by PCA (Principal Component Analysis). Based on the results of the research, there were 8 families of gastropod communities in St A and 6 families in St B. The most dominating families at the two observation stations were Potamididae and Neritidae. The highest abundance was found in St B at 290 ind/m2, while St A reached 180 ind/m2. The distribution pattern of gastropods is included in the grouping and even distribution criteria. From the results of PCA Gastropod analysis, it is closely related to dissolved oxygen content. This is related to the role of oxygen in the fulfillment of respiration and decomposition of organic matter.Keywords: Gastropods, Mangroves, Distribution patterns, Habitat preferences, Segara Anakan